Pergeseran Orientasi Sistem Pemilu Proporsional Terbuka dalam Praktik Penyelenggaraan Pemilu Legislatif - Adolof Seleky; Eivandro Wattimury (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
Elections are a means of exercising popular sovereignty guaranteed in the constitution. Constitutionally, the legislative election system adopted by Indonesia is a proportional representation system variant of the "list proportional reprecentation" (LPR) with an open list model. However, the Supreme Court Decision Number 57/P/HUM/2019 has changed the paradigm of election. The purpose of this study was to determine the implications of the Supreme Court's Decision Number 57/P/HUM/2019 on the electoral system in Indonesia. The research method is normative by using the statutory approach and conceptual approach to analyze qualitatively. The results showed that, a constitutional election system based on the mandate of the Constitutional Court Decree Number 22-24/PUU-VI/2008 is a proportional election system with an open list model, where the vote acquisition is based on the principle of "most votes" meaning that if the candidate wins the most votes the first cannot be inaugurated for some reason, it is automatically replaced by the second most votes winner, and so on. However the Supreme Court Decree Number 57/P/HUM/2019 states that the replacement of legislative candidates who are unable to remain remains the discretionary authority of the leadership of political parties. To avoid confusion in understanding the electoral system paradigm, in the future the Indonesian state must have the courage to apply the latest variant, "mixed member proportional" (MMP).